2015
DOI: 10.4103/0971-6203.170788
|View full text |Cite
|
Sign up to set email alerts
|

Use of image guided radiation therapy techniques and imaging dose measurement at Indian hospitals: A survey

Abstract: A national survey was conducted to obtain information about the use of image-guided radiotherapy (IGRT) techniques and IGRT dose measurement methods being followed at Indian radiotherapy centers. A questionnaire containing parameters relevant to use of IGRT was prepared to collect the information pertaining to (i) availability and type of IGRT delivery system, (ii) frequency of image acquisition protocol and utilization of these images for different purpose, and (iii) imaging dose measurement. The questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It would be prudent to consider the IGRT frequency based on individual patients rather than adopting a rigid protocol. In a national survey carried out by Deshpande et al., 68% of the radiation therapy centers adopted a patient‐specific approach for IGRT frequency; whereas, 18% and 14% adopted a daily and weekly approach, respectively 27 . Furthermore, Nabavizadeh et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be prudent to consider the IGRT frequency based on individual patients rather than adopting a rigid protocol. In a national survey carried out by Deshpande et al., 68% of the radiation therapy centers adopted a patient‐specific approach for IGRT frequency; whereas, 18% and 14% adopted a daily and weekly approach, respectively 27 . Furthermore, Nabavizadeh et al.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Although daily image guidance appears to be the best approach to mitigate errors, it might not be feasible for all patients, especially those in high-volume centers, as it increases the radiation therapy centers adopted a patient-specific approach for IGRT frequency; whereas, 18% and 14% adopted a daily and weekly approach, respectively. 27 Furthermore, Nabavizadeh et al reported that daily IGRT was practiced in almost all sites; however, no modi-fication of PTV margin was carried out based on frequency. 14 Even the American Society for Radiation Oncology (ASTRO) recommends a balance between the needs of the disease/technique, the imaging dose, and resource requirements without specifying a rigid protocol.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility of a more individual approach is the determination of positioning inaccuracy during the first three treatment fractions with subsequent adjustment of CBCT frequency (e.g., daily vs. weekly). Even though this approach is already standard procedure in many treatment centers [ 12 , 14 , 15 ], it lacks reliable evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The application of IGRT strategies in RT practice has grown exponentially in the past decade but internationally large variation has been reported in the availability and utilisation of IGRT in clinical practice [14][15][16]. Furthermore, IGRT modalities are both underused due to concerns regarding accumulated imaging dose [17] and potential time consuming nature of its execution [18].…”
Section: Introductionmentioning
confidence: 99%